PENGARUH SIKAP BELAJAR SISWA TERHADAP HASIL BELAJAR PKn KELAS VII DAN VIII DI SMP NEGERI 2 BATU GAJAH KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Rahayu, Sri; ', Gimin; ', Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is background by the learning attitude of student in SMP Negeri 2 Batu gajah Kecamatan Pasir Penyu Kabupaten Indragiri Hulu. Learning attitude change can be observed in the learning process, objectives, firmness and consistency towards something. This change is one indicator of the success of teachers in implementing the learning process. For that educators must create a lesson plan including the learning experience of students who made the attitudes of learning towards subjects become more positive.The formulation of the problem of this research is